Assessing the asymmetric effects of capital and money markets on economic growth in China - Mohammad Naim Azimi (Heliyon, 2022)
This study examines the effects of capital and money market predictors on economic growth in China using non-linear autoregressive distributed lags and dynamic multiplier methods. Applying asymmetric techniques is based on the hypothesized linear effects of finance on growth. Confirming the asymmetric nexus and long-run bounds amid indicators, the results demonstrate that positive (negative) shocks from money market rate decrease (increase) economic growth, while negative (positive) shocks from real interest rate and total liquidity increase (decrease) growth in the short-run. Besides, the results reveal that the shocks (positive and negative) from market capitalization and stock market turnover increase economic growth, while the shocks from total stock traded decrease growth both in the short and long runs. Moreover, the results of error-correction reveal a steady speed of adjustment of the short-run asymmetries to their long-run equilibrium, implying that improved financial systems attract sound financial projects, leading to sustainable and long-run economic growth. In light of the findings, relevant policy recommendations are discussed.